Indian medicinal plants : The plant profile and propagation aspects - Rao, Srinath; Ramakrishna, Akula (CRC PRESS: BOCA RATON)
"The demand for medicinal plants is increasing, and this leads to unscrupulous collection from the wild and adulteration of supplies. Providing high-quality planting material for sustainable use and thereby saving the genetic diversity of plants in the wild is important. In this regard, the in-vitro methods of propagation of some important medicinal plants are provided along with the traditional methods of propagation. Indian Medicinal Plants: The Plant Profile and Propagation Aspects offers a unique compendium of approximately 200 medicinal plant species from India with detailed taxonomic classifications based on the Bentham and Hooker system of classification. Salient Features: Provides traditional methods of propagation and discusses the propagation of medicinal plants Presents plant properties, plant parts and chemical constituents Describes the medicinal uses of approximately 200 medicinal plant species from India. This book is of special interest to practitioners of alternative medicine, students of Ayurveda, researchers and industrialists associated with medical botany, pharmacologists, sociologists and medical herbalists"--
Includes bibliographical references and index.
Keywords: Medicinal plants -- India